As leguminosas: da obscuridade à celebração - Sobral, José Manuel (Trabalhos de Antropologia e Etnologia, 2020)
Beans have been a fundamental part of human food for millennia. Yet, at least in Western societies, they were associated with poverty and rusticity, not appearing on the tables of the ruling classes. With the increase in the incomes of the western European population, in which the Portuguese is included, its consumption decreased while that of other foodstuffs increased (e.g., meat, once only available on a regular basis to the well-off). At the same time, in recent decades, beans have been associated with the rediscovery of regional and local cuisines, a movement that also finds a wide expression in Portugal. This text begins by providing some indications about the historical importance of beans in Portuguese food, looking at the social dimension of their consumption, and then briefly examining one of the gastronomic festivals that have emerged in the last decades, celebrating one of them: the grass pea.